2018
DOI: 10.1126/sciimmunol.aat4941
|View full text |Cite
|
Sign up to set email alerts
|

ZNF341 controls STAT3 expression and thereby immunocompetence

Abstract: Signal-transducer-and-activator-of-transcription-3 (STAT3) is a central regulator of immune homeostasis. STAT3 levels are strictly controlled and STAT3 impairment contributes to several diseases including the monogenic autosomal-dominant hyper-IgE syndrome (AD-HIES). We investigated patients of four consanguineous families with an autosomal-recessive disorder resembling the phenotype of AD-HIES, with symptoms of immunodeficiency, recurrent infections, skeletal abnormalities, and elevated IgE. Patients presente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
98
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 117 publications
(108 citation statements)
references
References 52 publications
7
98
0
3
Order By: Relevance
“…While this review was being revised, we and others reported patients with AR ZNF341 deficiency, which appears to be a phenocopy of AD STAT3 deficiency. This is understandable, as ZNF341 is a transcription factor that controls the expression, activation, and activity of STAT3 [194, 195]. One can therefore use the plural when referring to HIES, not because of AR DOCK8 and PGM3 deficiency, but because of AR ZNF341 deficiency that closely mimics AD STAT3 deficiency.…”
Section: Discussionmentioning
confidence: 99%
“…While this review was being revised, we and others reported patients with AR ZNF341 deficiency, which appears to be a phenocopy of AD STAT3 deficiency. This is understandable, as ZNF341 is a transcription factor that controls the expression, activation, and activity of STAT3 [194, 195]. One can therefore use the plural when referring to HIES, not because of AR DOCK8 and PGM3 deficiency, but because of AR ZNF341 deficiency that closely mimics AD STAT3 deficiency.…”
Section: Discussionmentioning
confidence: 99%
“…ZNF341 regulates STAT3 expression and its autoinduction during Th17 differentiation. ( B ) Key structural motifs within ZNF341 and the location of mutations in HIES patients identified by Beziat et al and Frey-Jacobs et al 1,2 .…”
Section: Figurementioning
confidence: 99%
“…By investigating patients from 10 families who present with symptoms resembling monogenic autosomal-dominant hyper-IgE syndrome (AD-HIES) but lack mutations in STAT3, two groups, Beziat et al 1 , and Frey-Jacobs et al 2 , identify a novel player in the pathway that regulates Th17 differentiation, and levels of IgE. The identification of the STAT3 mutations in humans with monogenic AD-HIES 3 , has emphasized the importance of this transcription factor in regulating Th17 cells, as well as the function of these cells in human health and disease.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations